Age Related Histological Study of Human Lacrimal Glands - Mamoona Hamid,Nabeela Akhter,Saadia Muzaffar,Tassaduq Hussain (Journal of Rawalpindi Medical College, 2015)
Background: To study the histological changes in human lacrimal glands in prereproductive, reproductive and post-reproductive ages. Methods: In this quantitative observational descriptive study specimens were taken from right sided orbital parts of 30 female human lacrimal glands of prereproductive (Group A), reproductive (Group B) and post-reproductive (Group C) ages (ten from each group). A 5 mm3 tissue was taken from the middle of each specimen. After processing, serial sections of 5μm thickness were made. All the slides were stained with Hemotoxylin/Eosin and PAS stain(for the study of basement membrane of acini). Capsule and connective tissue, glandular acini (type, number and diameter of acini) and basement membranes were studied. The significance between the means was calculated by one way ANOVA for age.To find the value of ‘p’ the difference was regarded statistically significant if the ‘p’ value was equal to or less than 0.05.A Duncan Multiple Range Test (MRT) for multiple comparison analysis was used. Results: The mean diameter of serous acini was maximum in Group B (reproductive group) whereas it was minimum in Group C (post reproductive group). There was decrease in mean number of acini in Group C (post-reproductive group) when compared with groups A (pre-reproductive group) and B (reproductive group) whereas maximum mean number was noted in Group B (reproductive group).The basement membrane with PAS staining was thin and magenta in colour in all the three groups. Conclusion: Lacrimal gland showed age related histological changes. These histological changes suggest a relation with keratoconjunctivitis sicca in postmenopausal women.